2010
DOI: 10.1002/jbm.b.31676
|View full text |Cite
|
Sign up to set email alerts
|

Small peptide (P‐15) bone substitute efficacy in a rabbit cancellous bone model

Abstract: P-15 is a synthetic 15-amino acid residue identical to the cell binding domain of type I collagen. P-15 can be adsorbed onto anorganic bovine bone mineral (ABM) and will enhance cell attachment and subsequent cell activation. Although ABM/P-15 has been studied as a bone graft substitute in the oral cavity, its use in orthopedic models has been limited. Thus, this study investigated the efficacy of ABM/P-15 treatment in a rabbit model of long bone cancellous healing. Defects were created in the distal femurs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…Consistent with the in vitro observation, ABM/P‐15 has been shown to promote early bone formation in a porcine skull model . More recently, ABM/P‐15 has been tested in extracranial orthopedic models, including cancellous long bone healing in rabbits and lumbar fusion . These studies support the effectiveness of ABM/P‐15 in promoting bone formation to the level of gold‐standard, autologous bone.…”
Section: Bioactive Collagen‐derived Peptide In Periodontal Regeneratisupporting
confidence: 71%
“…Consistent with the in vitro observation, ABM/P‐15 has been shown to promote early bone formation in a porcine skull model . More recently, ABM/P‐15 has been tested in extracranial orthopedic models, including cancellous long bone healing in rabbits and lumbar fusion . These studies support the effectiveness of ABM/P‐15 in promoting bone formation to the level of gold‐standard, autologous bone.…”
Section: Bioactive Collagen‐derived Peptide In Periodontal Regeneratisupporting
confidence: 71%
“…While a number of earlier studies have highlighted the role of P15 to enhance bone formation, relatively few have focused on how it might be utilized to increase implant integration. 10,11,14,26,28,29 Previous studies by Bhatnagar et al, 11 demonstrated enhanced binding of cells to P15-coupled polyglycolate (PGA) fibers and mesh, compared to the PGA alone. Kubler et al, 30 demonstrated cells plated on P15/ABM formed multilayered sheets that clustered around the hydroxyapatite particles in contrast to cells plated on the other substrates which formed only monolayer sheets on the graft particles.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, peptides have been used as practical catalysts in organic synthesis [29] as well as hosts for molecular recognition [30]. More recent researches have been focused on the applications of peptides to the preparation of compounds with technological properties [31], including biomaterials [32], hydrogelators [33], liquid crystals [34], biosensors [35], magnetic materials [36], photoluminescence materials [37], electronic devices [38], and mesoporous materials [39], among others.…”
Section: Introductionmentioning
confidence: 99%